Geminivirus-Mediated Genome Editing in Potato (Solanum tuberosum L.) Using Sequence-Specific Nucleases - Butler, Nathaniel M.; Baltes, Nicholas J.; Voytas, Daniel F.; Douches, David S. (Frontiers in Plant Science, 2016)
Genome editing using sequence-specific nucleases (SSNs) is rapidly being developed for genetic engineering in crop species. The utilization of zinc finger nucleases (ZFNs), transcription activator-like effector nucleases (TALENs) and CRISPR/Cas (clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated systems (Cas)) for inducing double-strand breaks facilitates targeting of virtually any sequence for modification. Targeted mutagenesis via nonhomologous end-joining has been demonstrated extensively as being the preferred DNA repair pathway in plants. However, gene targeting via homologous recombination remains more elusive but could be a powerful tool for directed DNA repair. To overcome barriers associated with gene targeting, a geminivirus replicon (GVR) was used to deliver SSNs targeting the potato ACETOLACTATE SYNTHASE1 (ALS1) gene and repair templates designed to incorporate herbicide-inhibiting point mutations within the ALS1 locus. Transformed events modified with GVRs held both point mutations that were capable of supporting a reduced herbicide susceptibility phenotype, while events transformed with conventional T-DNAs held no detectable mutations and were similar to wild-type. Regeneration of transformed events improved detection of point mutations that supported a stronger reduced herbicide susceptibility phenotype. These results demonstrate the use of geminiviruses for delivering genome editing reagents in plant species, and an approach to gene targeting in a vegetatively propagated species.